Vivências e memórias de um grupo de centenários no contexto de Passo Fundo - RS - Biolchi, Claudia da Silva (2012)
The aging of population is a phenomenon that involves many countries of the world, including Brazil. Among the elderly, comes a new group that is also getting old, the older elderly, and with them there is an increase in social demands for health and infrastructure to accommodate and ensure the quality of life of these people. The older elderly are part of a weakened population, and require greater input in care investments. The present study aimed to understand the meaning of old age and health selfperception in the perspective of a group of centennials, and to investigate functionality conditions. Nine elderly from the city of Passo Fundo-RS participated in the research, which inclusion criteria were to live in the urban or rural area, being one hundred years old or more, and having, upon being interviewed, cognitive conditions to answer to a questionnaire and/or being in the presence of either a family member or a caretaker. Data collection was performed through a semi-structured interview, using an instrument made of close-ended questions about the characterization of the participant, open-ended questions about the perceptions on a centennial life, and the Katz Índex to assess functionality. The results of the study were contemplated in two scientific productions in article mode, respectively entitled, Life and old age at one hundred years old: perceptions in the words of the elderly , and The functional capacity of a group of centennial elderly